Upregulation of SQSTM1/p62 contributes to nickel-induced malignant transformation of human bronchial epithelial cells. Issue 10 (2nd October 2016) - Huang, Haishan; Zhu, Junlan; Li, Yang; Zhang, Liping; Gu, Jiayan; Xie, Qipeng; Jin, Honglei; Che, Xun; Li, Jingxia; Huang, Chao; Chen, Lung-Chi; Lyu, Jianxin; et al.
ABSTRACT: Chronic lung inflammation is accepted as being associated with the development of lung cancer caused by nickel exposure. Therefore, identifying the molecular mechanisms that lead to a nickel-induced sustained inflammatory microenvironment that causes transformation of human bronchial epithelial cells is of high significance. In the current studies, we identified SQSTM1/p62 as a novel nickel-upregulated protein that is important for nickel-induced inflammatory TNF expression, subsequently resulting in transformation of human bronchial epithelial cells. We found that nickel exposure induced SQSTM1 protein upregulation in human lung epithelial cells in vitro and in mouse lung tissues in vivo . The SQSTM1 upregulation was also observed in human lung squamous cell carcinoma. Further studies revealed that the knockdown of SQSTM1 expression dramatically inhibited transformation of human lung epithelial cells upon chronic nickel exposure, whereas ectopic expression of SQSTM1 promoted such transformation. Mechanistic studies showed that the SQSTM1 upregulation by nickel was the compromised result of upregulating SQSTM1 mRNA transcription and promoting SQSTM1 protein degradation. We demonstrated that nickel-initiated SQSTM1 protein degradation is mediated by macroautophagy/autophagy via an MTOR-ULK1-BECN1 axis, whereas RELA is important for SQSTM1 transcriptional upregulation following nickel exposure. Furthermore, SQSTM1 upregulation exhibited its promotion of nickel-induced cell transformation through exerting an impetus for nickel-induced inflammatory TNF mRNA stability. Consistently, the MTOR-ULK1-BECN1 autophagic cascade acted as an inhibitory effect on nickel-induced TNF expression and cell transformation. Collectively, our results demonstrate a novel SQSTM1 regulatory network that promotes a nickel-induced tumorigenic effect in human bronchial epithelial cells, which is negatively controlled by an autophagic cascade following nickel exposure.